ChemInform Abstract: Magnetic Properties of the RbMnPO4 Zeolite‐ABW‐Type Material: A Frustrated Zigzag Spin Chain. Issue 42 (1st October 2013) - Nenert, Gwilherm; Bettis, Jerry Jr.; Kremer, Reinhard; Yahia, Hamdi Ben; Ritter, Clemens; Gaudin, Etienne; Isnard, Olivier; Whangbo, Myung‐Hwan
Abstract RbMnPO4 zeolite powder is prepared by solid state reaction of a stoichiometric mixture of Rb2CO3, MnO, and (NH4)H2PO4 (1.